The Role of Kamco in Resolving Nonperforming Loans in the Republic of Korea - He, Dong. (Washington, D.C. : International Monetary Fund, 2004)
This paper aims to provide a balanced assessment of Korea Asset Management Corporation's role in resolving nonperforming loans in the aftermath of the 1997-98 financial crisis. It argues that KAMCO's incentive to dispose of NPLs can be explained by a strong social desire for a recovery of public funds injected for financial sector restructuring. KAMCO's market-making role also helped overcome informational and coordination problems in the development of a market for distressed assets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet